Dampened copepod‐mediated trophic cascades in a microzooplankton‐dominated microbial food web: A mesocosm study. (25th November 2016) - Pree, Bernadette; Larsen, Aud; Egge, Jorun Karin; Simonelli, Paolo; Madhusoodhanan, Rakhesh; Tsagaraki, Tatiana Margo; Våge, Selina; Erga, Svein Rune; Bratbak, Gunnar; Thingstad, T. Frede
Abstract: Interactions of bottom‐up factors such as the availability of mineral and organic nutrients, and top‐down factors like predation and viral infection affect microbial communities of the pelagic food web. Hypothesis derived from previous experimental and modeling work suggest some general mechanisms on how these factors may be linked and call for an experiment to test interactions between (1) nitrogen source and diatom cell size, (2) bacterial growth rate limitation by mineral nutrients versus organic carbon, and (3) enhanced versus decreased predation pressure by copepods ( Calanus finmarchicus ). We performed a mesocosm experiment using a replicated three factor––two level full factorial design ( NH 4 + / NO 3 −, +/− glucose, and +/− copepods). Diatoms, pico‐ and nano‐sized autotrophs, prokaryotes, heterotrophic nanoflagellates, micro‐ and mesozooplankton abundances were monitored for 19 days. The main finding was a system that responded remarkably little to these manipulations with no effects of nitrogen source and only moderate effects of carbon treatments. Zooplankton manipulations had the strongest impact on microbial communities, but, opposite to our hypothesis based on previous studies, microzooplankton and diatoms increased during the first 7–10 days when mesozooplankton abundances were experimentally enhanced. We suggest that high abundances of dinoflagellates and ciliates and occurrence of rotifers, which dominated microzooplankton community in the first half of the experiment complicated trophic linkages between copepods, microzooplankton and diatoms. Apart from this dampened copepod mediated trophic cascade, we found tight couplings between communities of the microbial food web, with maxima of predator communities coinciding with low abundances of prey communities.